Dampak Education Mismatch terhadap Kinerja Karyawan BPR Sinar Mulia - Margareth Sylvia Sabarofek; Trian Wahyu Anggraeni (Departement of Mathematics Education, 2022)
This study aims to determine and explain the impact of education mismatch on the performance of BPR Sinar Mulia employees. This type of research is a qualitative research. The data analysis method that will be used in this research is descriptive research method. In this study, education mismatch is not a factor that hinders a person's performance. However, it takes a harder effort for employees with education mismatches to be able to adapt to their work and work environment, besides that one's education also determines the boundaries of employee career paths.